INTELLIGENT RECOGNITION SYSTEM ОF NANOMATERIAL STRUCTURE AND PROPERTY FORECASTING - V. M. Koleshko; E. A. Varabei; E. L. Prudnikova (Наука и техника)
The paper presents recognition results of nanomaterial structure and sensory properties while using a developed optical «electronic eye» (e-eye) «ISON-4» and an intelligent self-learning system «ISNM» with the purpose of non-invasive fast prediction of structurе, properties and quality in respect of nanomaterial production  during their synthesis and high-precision control of micro-nanosensory device manufacturing process.